Study of Photobleaching Mechanism in Methylene Blue Sensitized Gelatin Using a Single Beam UV-Vis. Fibre Optics Spectrophotometer - Sheng, Chan Kok; Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 2005)
In the present study, we have investigated the photobleaching of the methylene blue (MB) doped in Gelatin matrix using uv-visible fibre optic spectrophotometer. Illumination of the sample by uv-visible radiation resulted in a decrease of the absorption peak with the increasing of irradiation time. This indicates that upon irradiation MB dye molecule is photoreduced to its leuco form (colorless) of MB. The present experimental results indicate a slower photobleaching process occurring at higher concentration of dye doped in gelatin matrix. This study shows that the MB doped in gelatin solid matrix opens a new possibility in realtime holography applications.